Exploring astrobiology using in silico molecular structure generation - Meringer, Markus (Philos Trans A Math Phys Eng Sci, 2017)
The origin of life is typically understood as a transition from inanimate or disorganized matter to self-organized, ‘animate’ matter. This transition probably took place largely in the context of organic compounds, and most approaches, to date, have focused on using the organic chemical composition of modern organisms as the main guide for understanding this process. However, it has gradually come to be appreciated that biochemistry, as we know it, occupies a minute volume of the possible organic ‘chemical space’. As the majority of abiotic syntheses appear to make a large set of compounds not found in biochemistry, as well as an incomplete subset of those that are, it is possible that life began with a significantly different set of components. Chemical graph-based structure generation methods allow for exhaustive in silico enumeration of different compound types and different types of ‘chemical spaces’ beyond those used by biochemistry, which can be explored to help understand the types of compounds biology uses, as well as to understand the nature of abiotic synthesis, and potentially design novel types of living systems. This article is part of the themed issue ‘Reconceptualizing the origins of life’.